Vem bör stå för kostnaderna i förvaltningsprocessen?: En rättsanalytisk studie om förvaltningsprocessens kostnadsansvar - Meijering,Tammo (2025)
The absence of an immediate cost liability in administrative proceedings means that individuals are currently referred to a separate tort proceeding to be compensated for their litigation costs in administrative cases. The lack of direct compensation provisions in the Administrative Court Procedure Act [1971:291] (FPL) has several explanations. Firstly, it concerns how the com-mon foundations of the administrative and civil procedure were weakened through the 1940 legal procedure reform. Additionally, the practical design of administrative proceedings and the administrative courts duty to investigate ex officio have been used as arguments suggesting that there are no costs for the public to compensate. A final perspective has been that litigation costs are essentially a form of damages and therefore are mor appropriately compensated through a separate tort procedure. This traditional view was most recently affirmed by the Supreme Administrative Court (HFD) in HFD 2022 ref. 10. The approach to cost liability in administrative proceedings as reflected in HFD 2022 ref. 10 has been met with rights-based criticism, primarily on the grounds that this handling does not comply with the right to a fair trial under Article 6 of the European Convention on Human Rights (EKMR), nor with the right to judicial review under Chapter 2, section 11 of the Swedish Instru-ment of Government [1972:152] (RF). As a result of this criticism, which emerged following HFD 2022 ref. 10, the government has issued committee directive 2024:34 tasking an investigator with examining the possibilities for individuals to have cost liability determined within the administrative case itself. This legal-analytical study has therefore focused on several rights-related aspects of cost liability in administrative proceedings. The main research question has been how the upcoming inquiry´s proposal for cost liability in administrative proceedings best can align with the Access to Justice Theory (AtJ). AtJ theory posits that high litigation costs and imbalances in the party equality limits individuals access to effective legal remedies. To answer this main question, the study has sought to understand what historically legitimized the prin-ciple of cost neutrality in administrative proceedings, while also examining the handling of cost liability in relation to the guarantees of a right to a fair trial under art. 6[1] EKMR and the right to judicial review under Chapter 2, Section 11 RF. By comparing the principle of cost neutrality in administrative proceedings with the losers-pay-principle in civil litigation, the study has identified several differences regarding what justifies the principle of cost neutrality in administrative proceedings. The current handling of cost liability in administrative proceedings is not in conformity with the right to a fair trial under art. 6[1] EKMR, nor with the right to judicial review under Chapter 2, Section 11 RF. This conclusion is supported by rulings from the European Court of Human Rights in Steel & Morris v. The UK and Stankiewicz v. Poland, where imposed cost neutrality affected the party´s procedural equality. The European Court further ruled in Čerenius & Rinkevičius v. Lithuania that separate damage proceedings for cost liability limit individuals access to court. Similar conclusions have been drawn by the Swedish Supreme Court in NJA 2015 p. 374. According to AtJ theory, the current approach to cost liability in administrative proceedings is lacking in several aspects. This includes the fact that the handling of cost liability contributes to high litigation costs and that parties are procedurally unequal. The study has presented three concrete proposals that are deemed appropriate based on AtJ theory. The first is full reimbursement of costs in favour for individuals. The second is full reimbursement when the claim is fully upheld; in other cases, reimbursement is granted to the extent the claim is upheld. The third proposal is cost liability that arises in cases of error and negligence by administrative authorities. This is a way to influence the behaviour of administrative authorities in litigation and thereby mitigate pro-cedural inequality.
Keywords: Access to Justice; Förvaltningsrätt; Förvaltningsprocesslag; Förvaltningsprocessrätt; Kostnadsansvar; Kvittningsprincipen; Rättegångskostnader; Processkostnader